Developing Life Tables for Mauritian Population Using Lee-Carter Mortality Forecasts - Dhandevi, Woodun; Ming Kang, Ho (International Journal of Psychosocial Rehabilitation, 2020)
Appropriate life tables, also known as mortality tables, are highly important for pricing and reserving in insurance and pension industries. For the past few decades, remarkable improvements in life expectancies have been perceived which have further driven significant declines in mortality. From an actuarial perspective, the unremitting decrease in mortality rates has an impending effect on social security systems as well as on life insurance policies and pension plans. The main objective of this research is to develop unabridged life tables for the Mauritian population using the projected death rates from the Lee-Carter model. The empirical mortality dataset of Mauritian population from 1984 to 2016 are considered. The index level of mortality for each gender, shape and the sensitivity coefficients for the ages from 0 to 85 are obtained using Lee-Carter model. The Singular Value Decomposition (SVD) is used to forecast the general mortality index for the time period from 2017 to 2036.